2014
DOI: 10.4049/jimmunol.1300438
|View full text |Cite
|
Sign up to set email alerts
|

Binding of HLA-G to ITIM-Bearing Ig-like Transcript 2 Receptor Suppresses B Cell Responses

Abstract: Inhibition of B cells constitutes a rational approach for treating B cell–mediated disorders. We demonstrate in this article that the engagement of the surface Ig-like transcript 2 (ILT2) inhibitory receptor with its preferential ligand HLA-G is critical to inhibit B cell functions. Indeed, ILT2–HLA-G interaction impedes both naive and memory B cell functions in vitro and in vivo. Particularly, HLA-G inhibits B cell proliferation, differentiation, and Ig secretion in both T cell–dependent and –independent mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 45 publications
7
126
1
3
Order By: Relevance
“…In this context, studies by Naji et al (41,100) revealed that, through interaction with ILT2, HLA-G could inhibit the proliferation, differentiation and antibody secretion of activated B cells originating from peripheral blood and secondary lymphoid organs, such as tonsils, and HLA-G could also inhibit the proliferation of ILT2-bearing neoplastic B cell lines such as human B cell lymphomas (Raji, Daudi and Ramos), multiple …”
Section: Relevance Of Hla-g Expression In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, studies by Naji et al (41,100) revealed that, through interaction with ILT2, HLA-G could inhibit the proliferation, differentiation and antibody secretion of activated B cells originating from peripheral blood and secondary lymphoid organs, such as tonsils, and HLA-G could also inhibit the proliferation of ILT2-bearing neoplastic B cell lines such as human B cell lymphomas (Raji, Daudi and Ramos), multiple …”
Section: Relevance Of Hla-g Expression In Cancersmentioning
confidence: 99%
“…Due to its primary mRNA alternative splicing, seven HLA-G isoforms can be generated, Human Leukocyte Antigen-G (HLA-G) Expression in Cancers: Roles in Immune Evasion, Metastasis and Target for Therapy cells, and that this protective effect could be reversed by masking HLA-G antigens using HLA-G or its receptor-specific antibody (18,(38)(39)(40). It has been demonstrated that soluble HLA-G (sHLA-G) could inhibit B-cell proliferation, differentiation and immunoglobulin (Ig) secretion in both T-cell-dependent and -independent models of B-cell activation through the receptor ILT2 (41). To be noted, HLA-G5 was shown to inhibit phagocytosis and reactive oxygen species production of neutrophils through ILT4 (42).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The functions of HLA-G are oriented towards immune inhibition and induction of tolerance. Through direct binding to the inhibitory receptors Immunoglobulin-Like-Transcript (ILT)2 and ILT4, and Killer cell Immunoglobulin-Like Receptor (KIR)2DL4, 19 HLA-G mediates short-term inhibition of natural killer (NK) cells, 20 cytotoxic T-lymphocytes, 21 B cells, 22 and dendritic cells (DC) 23,24 and long-term induction of regulatory cells including HLA-G-expressing T regulatory (Treg) cells, 23 Human leukocyte antigen (HLA)-G is a non-classical HLA class I molecule with known immune-modulatory functions. Our group identified a subset of human dendritic cells, named DC-10, that induce adaptive interleukin-10-producing T regulatory type 1 (Tr1) cells via the interleukin-10-dependent HLA-G/ILT4 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It encodes molecules (seven isoforms) that are known ligands for inhibitory receptors found on the surface of different immune cell subpopulations, such as antigen-presenting cells, natural killer cells, B and T lymphocytes. [1][2][3][4][5] Besides its relevant physiological role in the induction of maternal-fetal tolerance, HLA-G can be expressed in numerous pathological situations, being either beneficial (autoimmune and inflammatory diseases, transplantation) or detrimental (infectious diseases, cancer) to the patient. [6][7][8] A tight regulation of HLA-G expression from fetal to adult life is then required for a fine adjustment of the immune response depending on the physiopathological context.…”
Section: Introductionmentioning
confidence: 99%